2022
DOI: 10.1186/s12960-022-00739-8
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid scale-up of COVID-19 training for frontline health workers in 11 African countries

Abstract: Background The global spread of the SARS-CoV-2 virus highlights both the importance of frontline healthcare workers (HCW) in pandemic response and their heightened vulnerability during infectious disease outbreaks. Adequate preparation, including the development of human resources for health (HRH) is essential to an effective response. ICAP at Columbia University (ICAP) partnered with Resolve to Save Lives and MOHs to design an emergency training initiative for frontline HCW in 11 African count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…3 Nursing and Midwifery Council of Ghana, Accra, Ghana. 4 Ghana Health Service, Accra, Ghana. 5 University for Development Studies, Tamale, Ghana.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Nursing and Midwifery Council of Ghana, Accra, Ghana. 4 Ghana Health Service, Accra, Ghana. 5 University for Development Studies, Tamale, Ghana.…”
Section: Abbreviationsmentioning
confidence: 99%
“…COVID-19 has created an unprecedented crisis worldwide, highlighting that a well-trained health workforce who can continuously update their skills in response to new pathogens and emergencies is imperative to a population's health [1][2][3][4]. However, health worker education in sub-Saharan Africa still faces numerous challenges that limit progress toward provision of quality care and attainment of Sustainable Development Goal-3 (Good Health and Well-being).…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Michelle Poimboeuf. The incorrect author name is: Michelle Poimbouef The correct author name is: Michelle Poimboeuf …”
Section: Correction: Human Resources For Health (2022) 20:43 101186/s...mentioning
confidence: 99%
“…Digital-based education can be conducted through websites, e-learning, webinars, or even material sharing through mobile communication media or social media. [13][14][15] This competency improvement was very much needed at the beginning of the pandemic because the new disease resulted in many gaps in knowledge, including how to treat patients, how to use Personal Protective Equipment (PPE), how to reduce virus transmission, and how to improve physical and psychosocial endurance. Digital-based education is widely carried out in the era of COVID-19, considering that the workload of nurses is growing along with the increase in the number of patients, making conventional training activities difficult to carry out.…”
Section: Introductionmentioning
confidence: 99%